A Rare Case Report of Impacted Primary First Molar below the First Premolar - Mouna Ben Salem; Abir Mannai; Yamina Elelmi; Fatma Masmoudi; Ahlem Baaziz (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Tooth impaction represents a disturbance in the normal eruption process, predominantly affecting permanent dentition, while its occurrence in primary teeth remains exceedingly rare. Such anomalies may lead to complications including delayed eruption of permanent successors, malocclusion, and potential damage to adjacent anatomical structures. However, limited evidence exists regarding the optimal management of impacted primary molars, particularly in atypical cases where the primary tooth is located inferior to its permanent successor. This study aims to report and evaluate the clinical management of a rare case involving an impacted mandibular first primary molar positioned beneath its succedaneous premolar, with emphasis on the outcomes of a conservative treatment approach. A 7-year-old male patient presenting with dental malposition underwent comprehensive clinical and radiographic examination, including panoramic radiography and computed tomography. Due to the close proximity of the impacted tooth to the mandibular canal and mental foramen, a non-invasive strategy consisting of periodic monitoring, space maintenance, and interceptive orthodontic treatment was implemented. Longitudinal follow-up over a five-year period demonstrated delayed but progressive development of the permanent premolar. Clinical and radiographic findings revealed initiation of eruption in 2024, followed by complete eruption in 2025 without surgical intervention or associated complications. These findings indicate that, despite initial developmental delay, spontaneous eruption remained achievable under careful supervision. In conclusion, conservative management with regular follow-up may represent a safe and effective alternative to surgical intervention in selected cases of impacted primary molars, particularly when anatomical risks are significant. This approach supports preservation of surrounding structures while allowing natural eruption processes, highlighting the importance of individualized, risk-based treatment planning in pediatric dentistry.